PENYULUHAN TENTANG BAHAYA FORMALIN TERHADAP TUBUH DI DESA SIDODADI - Linda Margata; Nurul Aini Siagian (INSTITUT KESEHATAN DELI HUSADA, 2021)
Food additives (BTM) especially additives are becoming increasingly significant in line with the advancement of innovation in the creation of engineered foods. One of the food additives permitted for use in food as indicated by Pastor Health Guidelines No. 722/Menkes/Per/IX/88 is an additive, where these additives can be described as food additives that can prevent or resist aging, fermentation or other food sources caused by microbial development. The use of additives in food should be appropriate, both type and dosage, but until now there is still a lot of work of additives that are prohibited for use in food and are not safe for welfare such as borax and formalin. Formalin is widely abused to protect food sources such as tofu and wet noodles. Formalin is really a fixing to protect bodies and organs and is extremely risky for wellbeing, in this manner in the Guideline of the Pastor of Wellbeing No. 722/Menkes/Per/IX/88 formalin is one of the fixings that are disallowed from being utilized as food added substances. Formalin ought not be utilized as a food additive, so there ought to be no buildup on food. The utilization of formaldehyde in food can cause harming in people with indications of trouble gulping, intense stomach torment, heaving, dying, circulatory issues and at high portions can bring about death. On the off chance that the formalin content in the body is high, it will respond artificially with practically all substances in the phone hence stifling cell capacity and causing cell demise bringing about body harming. Formalin harming can cause stomach bothering and hypersensitivities. Formalin also has carcinogens (cancerous) and mutagen properties (causing changes in cell function). In very high levels formalin can cause circulatory failure that boils down to death.